2017
DOI: 10.1038/s41529-017-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

Various effects of magnetite on international simple glass (ISG) dissolution: implications for the long-term durability of nuclear glasses

Abstract: Understanding the effect of near-field materials, such as iron corrosion products, on the alteration of vitreous nuclear waste is essential for modeling long-term stability of these waste forms in a geological repository. This work presents experimental results for which monoliths of International Simple Glass-a six oxide borosilicate glass-, with polished and unpolished cut sides, were aged for 70 days under oxic conditions at 90°C in a solution initially saturated in 29 SiO 2 at pH 7; then magnetite was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…Godon et al have shown that magnetite when in SON68 glass enhances glass alteration, first by the sorption of Si released from the glass onto magnetite surfaces, then by a second process that could be the precipitation of an iron silicate mineral or the transformation of magnetite into a more reactive phase like hematite or goethite. Similar results have also been reported by other researchers including Michelin et al and Neill et al . Interestingly, in all the studies reported on this topic, iron or its oxides have been added externally in the aqueous corrosion medium.…”
Section: Discussionsupporting
confidence: 88%
“…Godon et al have shown that magnetite when in SON68 glass enhances glass alteration, first by the sorption of Si released from the glass onto magnetite surfaces, then by a second process that could be the precipitation of an iron silicate mineral or the transformation of magnetite into a more reactive phase like hematite or goethite. Similar results have also been reported by other researchers including Michelin et al and Neill et al . Interestingly, in all the studies reported on this topic, iron or its oxides have been added externally in the aqueous corrosion medium.…”
Section: Discussionsupporting
confidence: 88%
“…[54][55][56] If fresh surfaces are created, it is then critical to assess if the passivating effect is re-established over time. Except in rare cases, 57 there is no evidence in the literature for a dramatic increase of nuclear glass alteration due to stress effects. The effects of radiation damage have been intensely studied.…”
Section: Overview Of Silicate Glass Corrosionmentioning
confidence: 99%
“…For instance, the literature reports several results of a detrimental effect of iron corrosion products on glass because the formation of the passivating layer is delayed or prevented by sorption of Si onto iron compounds and more importantly by precipitation of iron silicates. 18,21,57,82,83 Precipitation of silicate minerals is an additive process: in the case of phyllosilicate precipitation, experimentally sustained by the regular supply of Fe, Mg, Ni, or Co by the aqueous environment, the alteration rate of the glass increases proportionally to the amount of secondary precipitated phases. 84 When Mg is supplied by Mg-bearing minerals, both dissolution of the primary phase and transport of reactive species can affect the composition and the thickness of the passivating layer, and thus the alteration rate.…”
Section: Overview Of Silicate Glass Corrosionmentioning
confidence: 99%
“…Chemical reactions of nonequilibrium material, like glass, in nonequilibrium condition (corrosion) will be path‐dependent . It has been observed that the unpolished cut surface of international simple glass (ISG) exhibited enhanced alteration area compared with the polished surface in the presence of magnetite . It has been shown in an acid leaching experiment of soda lime silicate glass that the polished surface resulted in a thinner hydrated layer than the sawed surface .…”
Section: Introductionmentioning
confidence: 99%